2013
DOI: 10.1161/hypertensionaha.111.00055
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinase Enhances Big-Endothelin-1 Constriction in Mesenteric Vessels of Pregnant Rats With Reduced Uterine Blood Flow

Abstract: Abstract-Preeclampsia is a leading cause of maternal and fetal morbidity/mortality; however, the pathophysiological mechanisms are unclear. Vascular endothelial dysfunction in preeclampsia has been partially attributed to changes in endothelin-1 (ET-1). Several enzymes, including matrix metalloproteinases (MMPs; particularly MMP-2), cleave the inactive precursor big ET-1 (bET-1) to active ET-1. Notably, expression levels of MMP-2 have been shown to be on the increase in women who subsequently develop preeclamp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 30 publications
(28 reference statements)
2
44
1
Order By: Relevance
“…Interestingly, the expression levels of MMPs (particularly MMP-2 and MMP-1) have been shown to increase in women who subsequently develop PE. Abdalvand et al recently hypothesized that the increased MMP-2 expression leads to increased big-ET-1 conversion, and therefore increasing vasoconstriction [45]. They reported increased vascular contractility to big-ET-1 in the reduced uterine perfusion pressure (RUPP) model of PE that was likely attributable to upstream enzymatic pathways.…”
Section: The Et System In Pementioning
confidence: 99%
“…Interestingly, the expression levels of MMPs (particularly MMP-2 and MMP-1) have been shown to increase in women who subsequently develop PE. Abdalvand et al recently hypothesized that the increased MMP-2 expression leads to increased big-ET-1 conversion, and therefore increasing vasoconstriction [45]. They reported increased vascular contractility to big-ET-1 in the reduced uterine perfusion pressure (RUPP) model of PE that was likely attributable to upstream enzymatic pathways.…”
Section: The Et System In Pementioning
confidence: 99%
“…63 Others have shown that contractile responses to inactive precursor big ET-1 were increased in mesenteric arteries from this experimental model and that inhibition of matrix metalloproteinase, an enzyme that catalyzes the conversion of big ET-1 to ET-1, abolished the enhanced contractile responses. 65 Collectively, studies on endothelium-derived constrictors suggest that TxA 2 and ET-1 contribute to maternal vascular dysfunction in women with preeclampsia and in animal models with experimental preeclampsia. Neither the human nor the animal investigations, however, provide any insight into whether changes in TxA 2 and ET-1 production and actions contribute to the pathogenesis of preeclampsia or are consequences of the syndrome.…”
Section: Hypertensionmentioning
confidence: 99%
“…ET A R is mainly expressed in vascular smooth muscle (VSM) to induce vasoconstriction, whereas ET B R is predominately expressed in endothelial cells to induce the release of vasodilator substances, 14,15 and also plays a role in ET-1 clearance. 16 Although a role of ET-1 and its vasoconstrictor ET A R in modulation of cardiovascular-renal function during HTN-Preg has been suggested, 3,17-19 the role of vasodilator endothelial ET B R during Norm-Preg and HTN-Preg, and the post-ET B R mediators involved are less clear.…”
Section: Introductionmentioning
confidence: 99%